KONSEP DIRI STUDI KASUS DALAM PANDANGAN MASYARAKAT DI DESA PRENDUAN KACAMATAN PRAGAAN KABUPATEN SUMENEP - Mashodah Mashodah (Institut Dirosat Islamiyah Al-Amien Prenduan, 2019)
Gay or homosexuals who are considered not in accordance with social norms, identify individuals as deviant people. They cannot express themselves as gay or homosexual, in their work, such as working, socializing, having a partner and wanting to get married.The self-concept that is formed both positive and negative self concepts depends on the individual's acceptance of the other person's judgment and the individual's own judgment. Similarly, the views of the people in Prenduan fall into the category of good response. In an adjustment in the environment of a gay's level of adjustment to the community, the level of self-adjustment in this category has a good level of self-adjustment.This research was conducted with the aim of knowing self-concept in the view of the people in Prenduan Village, by adjusting themselves to the environment. This study uses qualitative research, with a case study method. Determination of informants in this study using purposive sampling method is the selection of data sources that are directly related to research. The method of data collection in this study used standardized interview interviews, non-participant observation, documentation. Data analysis researchers used the data analysis techniques of the Miles and Huberman models, checking the validity of the researchers' data by using source triangulation, by means of Member check.